2023
DOI: 10.1021/acsapm.3c00412
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Dynamic Crosslinking Polyurethane/PEG Shape-Stable Phase Change Materials Based on the Diels–Alder Reaction

Abstract: Phase change materials (PCMs) can absorb and release energy while keeping the temperature constant; hence, they play a crucial role in the thermal management field. Shape-stable phase change materials (SSPCMs) were synthesized by chemical crosslinking to address the liquid leakage problem of solid−liquid phase change materials (SLPCMs) during the phase change process. However, the abandoned SSPCMs cannot be reused and recycled, which seriously restricts their practical application. Herein, a polyurethane netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…2 a) disappeared 41 , accompanied by the presence of a new peak at 2266 cm −1 which vested in the typical absorption of –NCO groups. The peaks at 3332, 1717, and 1536 cm −1 should belong to the –NH–, amide, and C=O absorption in the newly formed urethane groups, respectively 42 . The analysis indicated that the terminal –OH groups of PEG were completely consumed and the –NCO groups were successfully introduced to the end of the PEG chain.…”
Section: Resultsmentioning
confidence: 99%
“…2 a) disappeared 41 , accompanied by the presence of a new peak at 2266 cm −1 which vested in the typical absorption of –NCO groups. The peaks at 3332, 1717, and 1536 cm −1 should belong to the –NH–, amide, and C=O absorption in the newly formed urethane groups, respectively 42 . The analysis indicated that the terminal –OH groups of PEG were completely consumed and the –NCO groups were successfully introduced to the end of the PEG chain.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al developed SSPCM using PU as supporting material and PEG as PCM to systematically examine the chemical composition and thermal storage capabilities. 25 The results revealed that SSPCM showed remarkable performance, with an enthalpy of 171.7 J/g without any leakage. Additionally, the structure, thermal, and chemical behavior of SSPCM remained unchanged after multiple thermal cycles and reprocessing.…”
Section: Polyurethanementioning
confidence: 94%
“…36 By incorporating waste stone fragments and employing low-toxic, low-flammability polymers in SSPCM production, there is an advancement towards aligning with the principles of a circular economy and diminishing the ecological footprint of manufacturing processes. 25 Therefore, encapsulating PCMs within waste plastics offers a dual benefit of mitigating plastic waste pollution while enhancing the energy storage capabilities of the materials. 34 The environmental impact of producing SSPCMs can be evaluated through life cycle analysis frameworks, which examine the ecological footprint at different stages of the product's life cycle, such as raw material extraction, manufacturing, usage, disposal, and recycling options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyurethane was recycled, but MDI, PTMG, furfuryl, and TMI could not be restored. 32 Lei et al prepared a recyclable PEG-based SSPCM through dynamic ionic crosslinking between grafted PEG and zinc acetate. PEG reacted with pyromellitic dianhydride (PMDA) to form the grafted PEG.…”
Section: Introductionmentioning
confidence: 99%